Welfare of zoo animals in Malaysia : current trends measures for improvement. - Sugnaseelan, Sumita; Sunil Kumar Sharma, Reuben
Over recent years, the issue of zoo animal welfare has been the focus of both the government and local NGOs in Malaysia. With over 40 public zoological parks and private collections, the emphasis for providing proper care and husbandry to wild animals in captivity is of pivotal concern. Following this, the new Wildlife Conservation Act 2010 (Act 716) has been put in place to supersede previous laws governing conservation, utilisation, trade and welfare of captive wild animals in the country. While many zoo operators have portrayed their genuine concern for the improvement of the welfare of wild animals held at their facilities, many are held back with constraints of space and budget. As such, audits were carried out at most of the major establishments to evaluate the current situation and recommendations have been issued on how these obstacles may be overcome within a reasonable period of transition time. The first phase of the remedial process will involve the large mammals and primates, with emphasis on providing a suitable physical, physiological and psychological environment, provision of a suitable diet, and timely veterinary care. Specific issues highlighted include the refurbishment and upgrading of the enclosures to address space requirements of outdoor exhibits and indoor night stalls, provision of suitable furniture, substrate and enrichment according to the needs of the species. Emphasis will also be given to the feeding regime and diet, improvement in overall sanitation of the enclosures, management of zoo records, designing prophylaxis and prevention programmes, improvement of waste management, protocols for quarantine and disease monitoring, and the employment of either a permanent or named consultant veterinary surgeon. The second phase will cater for small mammals, birds and herpetofauna. lt is envisaged that such a programme, although laden with many challenges, will ensure the gradual improvement in the welfare standards of wild animals held in zoological facilities in the country.